Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.4172/2329-6631.1000179
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Clinical Significance of Potential Drug-Drug Interactions at Ayder Referral Hospital, Northern Ethiopia

Abstract: Introduction: Clinically significant drug-drug interactions reduce effectiveness of drugs or cause fatal adverse events. Although harmful drug interactions are preventable, clinicians' recognition and detection of drug interactions is not optimal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Different studies were also supported as polypharmacy and comorbid disease increases the likelihood of the occurrence of potential DDIs [15,33,42,43]. In the review, taking five or more medications was an important factor Fig.…”
Section: Factors Descriptionmentioning
confidence: 95%
See 1 more Smart Citation
“…Different studies were also supported as polypharmacy and comorbid disease increases the likelihood of the occurrence of potential DDIs [15,33,42,43]. In the review, taking five or more medications was an important factor Fig.…”
Section: Factors Descriptionmentioning
confidence: 95%
“…No of prescribed drugs (Polypharmacy) Patients taking three or more than three concomitant drugs are at higher risk of the occurrence of potential DDIs [27,28] There is an association of the occurrence of one or more potential DDIs with the number of medications prescribed per patient who took more than four medications [35] Polypharmacy (five or more medications) is an important factor which leads to potential DDIs [5, 29-31, 33, 34] Co-morbid disease Co-morbid condition independently increased the potential DDIs almost 2-folds [33] Age Older age was found to be predisposing factors for the occurrence of DDI [5,28,30,31] Potential DDIs were occurring more frequently in the age group of 2-6 years than any other age group of the pediatric population [29] Hospital stay The chance of taking multiple drugs increases with longer stays (greater than or equal to seven) in the hospital, which in turn increases the risk for potential DDIs [5] International Normalized ratio (INR value) Increase in international normalized ratio value was found to be strongly associated with DDI and hence the risk of bleeding [32] Footnote: Ten studies did not report the mechanisms of drug-drug interaction identifying actual DDIs is much more complicated than potential DDIs. The analysis showed that the occurrence of potential DDIs in the inpatient and outpatient settings reported by studies (inpatient: 73.2% (95% CI: 60.8 to 85.7%; outpatient: 80.0% (95% CI: 58.9 to 101.1%; inpatient and outpatient setting: 32.6% (95% CI: 30.6 to 34.6%).…”
Section: Factors Descriptionmentioning
confidence: 99%